Parenting stress in parents of children with refractory epilepsy before and after vagus nerve stimulation implantation - Sung-Tse Li; Nan-Chang Chiu; Yung-Ting Kuo; Ein-Yiao Shen; Pei-Chieh Tsai; Che-Sheng Ho; Wen-Hsiang Wu; Juei-Chao Chen; Chuan-Yu Wang; Yung-Ting Kuo; Huei-Shyong Wang; Kuang-Lin Lin; et al. (Elsevier, 2017)
Objectives: The purpose of this study was to evaluate parenting stress in parents of children with refractory epilepsy before and after their children received vagus nerve stimulation (VNS) implantation. Methods: Parents of children with refractory epilepsy completed the Parenting Stress Index (PSI) under a psychologist's assessment before and at least 12 months after their children received VNS implantation. The PSI questionnaire measures parenting stress in two domains; a parent domain with seven subscales, and a child domain with six. Age, gender, epilepsy comorbidity, VNS implantation date, seizure frequency, and anticonvulsant history before and after VNS implantation were obtained from reviews of medical charts. Results: In total, 30 parents completed the first and follow-up PSI questionnaires. Seventeen of their children (56.7%) were boys. The children aged from 1 to 12 years (7.43 ± 3.59 years, mean ± SD). After VNS implantation, the mean total parenting stress scores decreased from 282.1 ± 38.0 to 272.4 ± 42.9. A significant decrease was found on the spouse subscale of the parent domain. For the parents of boys, the mean total parenting stress scores decreased significantly. The mean total parenting stress scores also decreased significantly for parents of epileptic children without autism and who did not taper off the number of different anticonvulsants used after VNS. Conclusions: VNS is an advisable choice to treat refractory epilepsy. Our study showed that 12 months or more after VNS implantation, seizure frequency and parenting stress typically decreased. However, in some special cases the parenting stress may increase, and external help may be required to support these patients and their parents. Key Words: children, refractory epilepsy, parenting stress, vagus nerve stimulation